Comments on Eisenberg, Differing Perceptions of Attorney Fees in Bankruptcy Cases - Lloyd A. Palans (Washington University Law Quarterly, 1994)
My problem is not with the right to criticize fees or the "perceptions" of lawyers or judges with respect to bankruptcy fees. After all, this is America. But, I am compelled to ask: Why? For what purpose? At some point, academicians must reintroduce themselves to reality. The true test of legal scholarship-whether it has advanced legal thought, theory and analysis-is, after all, what this Interdisciplinary Conference is about.
Keywords: Bankruptcy; Lawyers – Fees; Bankruptcy reorganization